The problem of how to train members of ethics committees - Dryla, Olga (Diametros, 2009)
The article considers a problem that has not yet found a satisfactory solution in Poland, that of how to train members and candidates for membership in bioethics commissions. The author proposes that discussions be undertaken in the light of the suggestions of the World Health Organization and the experience of other European countries.